The Criminalization of Poverty: Analyzing Socioeconomic Bias in Penal Policies - Waluyo, Dadi; Sumardi, Sumardi; Santosa, Tomi Apra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze how criminal policies systematically show socio-economic biases that have an impact on the criminalization of poor groups. Through a qualitative approach with policy analysis methods and literature studies, this study evaluates the relationship between individual economic status and treatment in the criminal justice system. The findings show that a number of criminal policies, such as penalties for misdemeanors, pre-trial detention policies, and bail systems, tend to disproportionately burden poor individuals. On the other hand, individuals with better economic backgrounds have access to legal protections and greater opportunity for sentence mitigation. The results of this study reveal the reproduction of structural inequality through criminal law policies, which not only strengthen economic marginalization but also hinder social mobility. The study recommends the need for social justice-based criminal policy reform and a non-punitive approach to poverty-related offenses, in order to create a more equitable and inclusive legal system.